Med božjo iskrico in lastno smrtjo - Kumerdej, Mojca (Primerjalna književnost, 2009)
In spite of contemporary literary theories, which have taken off writer's laurels of the authorship as un unrepeated original synthesis of form and content and have implanted doubt about creativeness as an effect of author's will, skills and intention, one of the key features of the traditional authorship concept is kept in the creative process - narcissism as a prolongation of the infantile period and with it connected feeling of creation ability within the field of unlimited possibilities. The paradox of the literary - and perhaps of any artistic creativeness - is in this, that a writer feels the most on himself and for himself in those creative periods, when it seems to him that, pervaded by unlimited, ocean feeling, he is surpassed by his own creativeness, that thus he alone is not the one who controls the process, but is "merely" the means of a creative process.
Keywords: literarna teorija; literary theory; avtor; avtorstvo; umetniška ustvarjalnost; ustvarjalni proces